Governance of partnership between health and social services: the experience in Somerset. - Peck E; Gulliver P; Towell D (Health & Social Care in the Community, 2002)
As one part of a larger study of the integration of mental health and social care, the present paper explores the role of the Joint Commissioning Board in the governance arrangements for health and social partnership in Somerset, UK. A short review of the literature on joint planning and joint commissioning revealed that such partnership has proved problematic, and that the role of non-executive directors and councillors is usually overlooked. Furthermore, the research on corporate boards suggests that their performance does not match the prescriptions made for them. Following a description of the methodology of the study, the present paper reports the findings of the activity of the Joint Commissioning Board from three data sources: (1) observation of meetings; (2) analysis of documentation; and (3) participant interviews. All three sources support the view, put forward in the Discussion section, that the Board does not play a proactive role in the setting and monitoring of policy and priorities. Nonetheless, it is argued, the Board plays a central and constructive role in the governance of partnership: as the symbol of interagency partnership; as the vehicle for sustaining commitment to mental health; and as the method of bringing additional elements of public accountability to the commissioning and providing of health and social care. Locating this ritual function of the Board within the broader sociological literature, the Discussion section goes on to suggest the implications both for the future of governance of partnership and for further research in this area.